TRAUMATIZATION BY LAMPREYS OF SOCKEYE SALMON ONCORHYNCHUS NERKA (WALBAUM, 1792) IN THE MEYNYPIL’GYN LAKE-RIVER SYSTEM (KORYAK COAST OF CHUKOTKA) - E. V. Golub’; A. P. Golub’ (Известия ТИНРО)
Data on traumatization of sockeye salmon Oncorhynchus nerka spawners in the Meynypil’gyn lake-river system by lampreys are presented on results of observations in 1998– 2018. Features and localization of injuries are described comparing the injuries of males and females and biological parameters of fish with and without the injuries. In the Meynypil’gyn lake-river system, relative to other areas of Russian Far East, the portion of fish with injuries from lampreys is medium for sockeye salmon, and low for pink salmon Oncorhynchus gorbuscha and charr Salvеlinus malma. Judging by size of the wounds, the injuries were caused mostly by arctic lamprey Entosphenus tridentatus. Generally, about 68 % of sockeye spawners were attacked by lampreys during their pre-spawning migrations just before entering the fresh waters, but the percentage (P) depends on length (L) of fish: P = 1.2026 . L + 1.2192 (R2 = 0.879). So, the portion of injured fish increased from 2.7 % for the sockeye producers with length < 500 mm to 31.2 % for those with length 671–680 mm. Mean size and weight of the male and female sockeye spawners with traces of lampreys were statistically significantly higher than these parameters for the fish without injuries. The males injured by lampreys were larger than the males without injures in 18 mm and 295 g, the females — in 5 mm and 80 g, on average. Sockeye females had weaker and less numerous damages, so their portion among the fish with 1 injury was 45.4 %, among the fish with 2 injuries — 42.9 %, among the fish with 3 or more injures — 37.0 %. Besides, mean size of the injured sockeye increased with a number of injures and for the groups with 1, 2, and 3 or more injures it was for females: 604, 608, and 613 mm, for males: 655, 667, and 674 mm, respectively. Such dependencies of alive fish traumatization on their size are caused by higher mortality of small fish after lampreys attacks. There is concluded that arctic lamprey affects significantly on sexual and size composition of sockeye spawners in the Meynypil’gyn lake-river system providing selection of fish with larger size and weight, in particular males.